Efficacy and safety of total glucosides of paeony in the treatment of systemic lupus erythematosus: A systematic review and meta-analysis - Gong, Xiaohong; Li, Huan; Guo, Hongtao; Wu, Shangwen; Lu, Chaoqun; Chen, Yiming; Li, Songwei (Frontiers in Pharmacology, 2022)
Background：Total glucosides of Paeony (TGP), extracted from the Chinese medicine Paeonia lactiflora Pall, has been proved to be effective in various autoimmune diseases. We aim to systematically evaluate the efficacy and safety of TGP combined with different conventional therapeutic agents in the treatment of systemic lupus erythematosus (SLE). Methods: Eight databases were searched for randomized controlled studies of TGP for SLE. The search time was set from the establishment of the databases to March 2022. The risk of bias was assessed by Cochrane Evaluation Manual (5.1.0), the RevMan5.3 software was used for meta-analysis, and the certainty of the evidence was assessed by GRADE methodology. Results: A total of 23 articles were included, including 792 overall patients in the treatment group and 781 patients overall in the control group. The meta-analysis results showed that TGP combined with conventional treatments was superior to the conventional treatments in reducing the SLE disease activity and incidence of adverse reactions (SMDTGP+GC+CTX = -1.98, 95%Cl = [-2.50, -1.46], p <0.001; SMDTGP+GC+HCQ = -0.65, 95%Cl = [-1.04, -0.26], p <0.001; SMDTGP+GC+TAC = -0.94, 95%Cl = [-1.53, -0.34], p <0.05; SMDTGP+GC = -1.00, 95%Cl = [-1.64, -0.36], p <0.05; RRTGP+GC+CTX = 0.37, 95%Cl = [0.21, 0.64], p <0.001). The results also showed that TGP helped improve other outcomes related to SLE disease activity, such as complement proteins (C3, C4), immunoglobulins (IgA, IgM, IgG), ESR, CRP, 24h urine protein and recurrence rate. In addition, TGP may also be effective in reducing the average daily dosage of glucocorticoids (GC) and the cumulative dosage of cyclophosphamide (CTX). The certainty of the evidence was assessed as moderate to low. Conclusion: TGP is more effective and safer when used in combination with different conventional therapeutic agents. It helped reduce the disease activity of SLE and incidence of adverse reactions. However, considering the high risk of bias, it still need to be confirmed in high-quality trials.